2017
DOI: 10.1016/j.exphem.2017.06.163
|View full text |Cite
|
Sign up to set email alerts
|

Sca-1 expression level identifies quiescent hematopoietic stem and progenitor cells

Abstract: SUMMARYBlood cell generation depends on continuous cellular output by the sequential hierarchy of hematopoietic stem cell (HSC) and progenitor populations that all contain quiescent and actively cycling cells. Hematopoietic stem and progenitor cells (HSPCs) express the surface molecule Stem cell antigen 1 (SCA-1/LY6A). Using histone 2B-red fluorescent fusion protein label retention and cell-cycle reporter mice, we demonstrate that high SCA-1 expression (SCA-1 hi ) identifies not only quiescent HSCs but quiesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…At 24 and 48h, CD48 correlated negatively to self-renewal and positively to production of SLAM+MEPs when IL-3 and IL-6 is added. As cocktail composition did not have a major impact on the relationship between familial fate and ancestral expression of Sca-1 and c-Kit, these results were suggestive that c-Kit and Sca-1 expression levels of SLAM-HSCs act as intrinsic markers for both familial progression and differentiation with high Sca-1 expression and low c-Kit expression leading to less division [35][36][37] and less differentiation [38], and potentially resulting in better engraftment [35,36,38]. While low ancestral CD48 expression level has been reported to result in less division [39,40], our data indicates its relationship to differentiation is dependent on extrinsic signals.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…At 24 and 48h, CD48 correlated negatively to self-renewal and positively to production of SLAM+MEPs when IL-3 and IL-6 is added. As cocktail composition did not have a major impact on the relationship between familial fate and ancestral expression of Sca-1 and c-Kit, these results were suggestive that c-Kit and Sca-1 expression levels of SLAM-HSCs act as intrinsic markers for both familial progression and differentiation with high Sca-1 expression and low c-Kit expression leading to less division [35][36][37] and less differentiation [38], and potentially resulting in better engraftment [35,36,38]. While low ancestral CD48 expression level has been reported to result in less division [39,40], our data indicates its relationship to differentiation is dependent on extrinsic signals.…”
Section: Resultsmentioning
confidence: 82%
“…For ST-HSCs, the ancestral level of CD48 and Sca-1 consistently correlated negatively and positively, respectively, with de-differentiation to SLAM-HSC in the cocktail with IL-3 and IL-6 at both time points ( Figure 4E and S7, and Supplementary Table 6). Differentiation to GMP, which occurred only in 48h data, correlated positively and negatively with the ancestral level of CD48 and Sca-1 respectively ( Figure 4E) [37]. Therefore, differentiation to GMP from ST-HSC was dependent on the parental level of CD48 and Sca-1, whereas the dedifferentiation to SLAM-HSC is dependent on both extrinsic factors (IL-3 and IL-6) and the intrinsic ancestral level of CD48 and Sca-1.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Among HSCs with high background fluorescence from all three different repressed H2B-FP mouse strains under investigation, we observed significantly higher expression of Sca-1, CD201 and CD150 as well as concordant down-regulation of CD34, CD48 and CD117 (Figure S1C-E) compared to cells without H2B-FP background fluorescence. This expression pattern of surface markers has been previously correlated to increased quiescence and repopulation activity of HSCs (Beerman et al, 2010;Grinenko et al, 2014;Kent et al, 2009;Kiel et al, 2005;Morcos et al, 2017;Osawa et al, 1996;Sato et al, 1999;Säwén et al, 2016;Shin et al, 2014;Wilson et al, 2015). To further investigate the cell cycle status of HSPCs in relation to H2B-GFP background fluorescence, we analyzed the BM of un-induced Ki67 RFP/wt /R26 rtTA/wt /Col1A1 H2B-GFP/wt mice, in which Ki67-RFP expression reports cycling cells (Basak et al, 2014;Morcos et al, 2017).…”
Section: Primitive Hspcs Exhibit Higher Levels Of Leaky H2b-fp Backgrmentioning
confidence: 98%
“…The multi-potent and self-renewing hematopoietic stem cells (HSCs) reside at the top of the hematopoietic hierarchy and can give rise to all blood lineages throughout the life of an individual (Eaves, 2015). Numerous studies have demonstrated heterogeneous cell cycle activity within the HSC population (Foudi et al, 2008;Glauche et al, 2009;Morcos et al, 2017;Passegué et al, 2005;Qiu et al, 2014;Säwén et al, 2016;Takizawa et al, 2011;Wilson et al, 2008). A concept of deeply quiescent (also termed `dormant´) and actively cycling HSCs has been inferred from experiments investigating mitotic history by means of labeled nucleotide analogs (e.g.…”
Section: Introductionmentioning
confidence: 99%